Lessons from exome sequencing in prenatally diagnosed heart defects: A basis for prenatal testing. Issue 5 (28th March 2019) - Westphal, Dominik S.; Leszinski, Gloria S.; Rieger‐Fackeldey, Esther; Graf, Elisabeth; Weirich, Gregor; Meitinger, Thomas; Ostermayer, Eva; Oberhoffer, Renate; Wagner, Matias
Abstract : Congenital heart defects (CHDs) are the most common birth defect with 30%‐40% being explained by genetic aberrations. With next generation sequencing becoming widely available, we sought to evaluate the clinical utility of exome sequencing (ES) in prenatally diagnosed CHD. We retrospectively analyzed the diagnostic yield as well as non‐conclusive and incidental findings in 30 cases with prenatally diagnosed CHDs using ES, mostly as parent‐child trios. A genetic diagnosis was established in 20% (6/30). Non‐conclusive results were found in 13% (4/30) and incidental findings in 10% (3/30). There was a phenotypic discrepancy between reported prenatal and postnatal extracardiac findings in 40% (8/20). However, none of these additional, postnatal findings altered the genetic diagnosis. Herein, ES in prenatally diagnosed CHDs results in a comparably high diagnostic yield. There was a significant proportion of incidental findings and variants of unknown significance as well as potentially pathogenic variants in novel disease genes. Such findings can bedevil genetic counseling and decision making for pregnancy termination. Despite the small cohort size, our data serve as a first basis to evaluate the value of prenatal ES in CHD for further studies emerging in the near future. Abstract : Exome sequencing in prenatally diagnosed congenital heart defects (CHDs) results in a comparably high diagnostic yield. Additional postnatal findings did not alter the genetic diagnosis. This study serves as a first basis to evaluate the value of prenatal exome sequencing in cases of CHD for further studies emerging in the near future.